CIPP-Based Evaluation of Physical Education, Sports, and Health Learning Implementation in a Vocational Secondary School - Muhammad Ghaluh; Eval Edmizal; Yendrizal Yendrizal; Kristian Burhan (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Physical Education, Sports, and Health (PJOK) in vocational high schools often occupies a complementary role despite its important contribution to students' physical, social, and psychological development. This study evaluates the implementation of PJOK learning at SMKN 6 Padang, Indonesia, using Stufflebeam's Context, Input, Process, and Product (CIPP) evaluation model. A descriptive design was employed with a population of 997 Grade X and XI students and PJOK teachers. A sample of 90 students was selected through stratified random sampling using the Slovin formula (d = 0.1). Data were collected through validated Likert-scale questionnaires (teacher reliability = 0.940; student reliability = 0.790) and semi-structured interviews with three PJOK teachers, then analyzed using descriptive percentage analysis. The findings indicate that 78.9% of students rated PJOK implementation as "good," 15.6% as "very good," and 5.6% as "enough," with no negative ratings. Teacher interviews confirmed that learning planning was aligned with the Merdeka Curriculum, teaching methods incorporated varied physical activities, and assessment covered cognitive, affective, and psychomotor domains. However, implementation was constrained by limited sports facilities, scheduling issues, weather conditions, and large class sizes. This study provides empirical evidence on PJOK implementation in vocational high schools and extends the CIPP evaluation literature by triangulating quantitative student perceptions with qualitative teacher perspectives under the new national curriculum. The findings also offer implications for teaching practice, school policy, and future evaluative research.